INTRODUCTION TO TEACHING TEACHERS IN MODULE MAKING TRAINING AT SMPN30 PADANG - vivi fitriani; Diana Susanti; Liza Yulia Sari (Universitas PGRI Sumatera Barat, 2021)
The purpose of this activity is that the teacher has knowledge about making modules that will be used as teaching materials in the learning process. This activity is a dissemination of the research that has been carried out by the team, namely the development of Project Based Learning modules in Biology Learning Media Lectures. This service consists of several stages. First, the lecturer team as resource persons conveyed material related to teaching materials in general first, then followed by various learning resources and modules in particular. The second was followed by discussion and question and answer.